2004
DOI: 10.1038/sj.onc.1207757
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B1 depletion inhibits proliferation and induces apoptosis in human tumor cells

Abstract: Cyclin B1 is the regulatory subunit of M-phase promoting factor, and proper regulation of cyclin B1 is essential for the initiation of mitosis. Increasing evidence indicates that the deregulation of cyclin B1 is involved in neoplastic transformation, suggesting the suppression of cyclin B1 could be an attractive strategy for antiproliferative therapy. In the present work, we analysed the impact of small interfering RNAs (siRNAs) targeted to cyclin B1 on different human tumor cell lines. Cyclin B1 siRNAs reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
156
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(173 citation statements)
references
References 16 publications
(23 reference statements)
15
156
1
Order By: Relevance
“…We then tested the role of cyclin B1 and cyclin E1 directly by blocking the expression by RNAi. siRNA for cyclin B1 reduced the amount of cyclin B1 protein and reduced the number of cells in primary apoptosis at 24 and 48 h. It has been previously reported that reduction of cyclin B1 protein by RNAi (without further treatment with cytotoxic agents such as CPT) increases the percentage of cells in G2/M-phase and initiates apoptosis by 48 h (Yuan et al, 2004). In the results reported here, we also detected a cell cycle arrest and an increase in sub-G1 cells after siRNA treatment at 48 h ( Figure 6b).…”
Section: Discussionmentioning
confidence: 85%
“…We then tested the role of cyclin B1 and cyclin E1 directly by blocking the expression by RNAi. siRNA for cyclin B1 reduced the amount of cyclin B1 protein and reduced the number of cells in primary apoptosis at 24 and 48 h. It has been previously reported that reduction of cyclin B1 protein by RNAi (without further treatment with cytotoxic agents such as CPT) increases the percentage of cells in G2/M-phase and initiates apoptosis by 48 h (Yuan et al, 2004). In the results reported here, we also detected a cell cycle arrest and an increase in sub-G1 cells after siRNA treatment at 48 h ( Figure 6b).…”
Section: Discussionmentioning
confidence: 85%
“…19 CCNB1, the regulatory subunit of MPF, could specifically increases the activity of CDK1, further leading to a strong proliferation promotion in a variety of cancer cells. 10,20 Studies have also revealed that CCNB1 is highly expressed in various primary tumors, 5-9 including colorectal cancer. 21 These data highlight the potential pivotal roles of CCNB1 both in the development and progression of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the idea that cyclin B2 could not compensate for a lack of cyclin B1. However, while cyclin B1 depletion by RNA interference in cultured cells has been shown to inhibit proliferation by arresting cells in G 2 /M, (Yuan et al, 2004(Yuan et al, , 2006, the degree of cell growth inhibition is dependent on the cell type and, surprisingly, human primary cells do not exhibit any defect, despite a quasi-complete inhibition of cyclin B1/CDK1 kinase activity (Yuan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%